Motivation to maintain sobriety among residents of sober living recovery homes - Polcin DL; Korcha R (Dove Medical Press, 2015)
Douglas L Polcin, Rachael KorchaAlcohol Research Group, Public Health Institute, Emeryville, CA, USABackground: The study of motivation in the substance abuse field has typically examined the extent to which substance users want to quit or reduce substance use. Less frequently examined is the desire to maintain sobriety after achieving abstinence. The current study examined motivation to maintain sobriety among residents of sober living houses (SLHs), a type of recovery home for individuals with alcohol and drug problems. Previous research on this population showed favorable longitudinal outcomes over 18 months. Resident views about the costs of not using substances (ie, the difficulties encountered when not using), as well as the perceived benefits of not using, were strong predictors of substance use outcomes.Methods: This study adds to these findings by conducting two focus groups with individuals familiar with the structure and day-to-day operations of SLHs, including administrators of SLH organizations, owners, and peer managersResults: Focus group results supported the importance of costs and benefits as motivational forces influencing abstinence. However, participants also emphasized characteristics of the sober living recovery environment as important factors influencing motivation. Interactions among recovering peers offer unique opportunities for feeling understood, recognizing vulnerability in others, identifying with the recovery processes of others, receiving supportive confrontation, and engaging in mutual accountability. These experiences are important elements of motivation that become activated by involvement in the SLH environment and are difficult to replicate outside of that context.Conclusion: In addition to recognizing how motivation can be enhanced by addressing costs and benefits experienced by individuals, operators of recovery homes need to understand motivation as a function of the recovery home social environment. Additional studies are needed on motivation as a longitudinal construct in a variety of peer-oriented environments. Studies are also needed to better specify interactions within SLHs that increase and hinder motivation among different types of residents.Keywords: recovery residence, sober living house, social model, social environment